(untitled) (Informatica, 2022)
Measuring network performance is essential in computer networks, and benchmarking may not be effective for installation in peripheral devices, resulting in replacing those devices and thus increasing cost. In light of this, it is better to have a software system for the network to see its performance rather than the actual design. In this paper, we have developed negative network tomography techniques to infer correlation-level aberrations such as excessive loss rates and delays from path-level measurements. Our system involves placing packet probes in passive monitoring devices on strategic links within the network to learn about network performance with the identification of missing and transmitted packets, and to keep the cost of monitoring and communications infrastructure low. An intuitive graphical user interface(GUI) represents this work provided along with a variety of data, metrics, and statistics related to network results, and this work can be a useful guide for network researchers or other programmers to analyze their networks and understand how to calculate network performance.